2010
DOI: 10.1016/j.cell.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Cell Signaling by Receptor Tyrosine Kinases

Abstract: Recent structural studies of receptor tyrosine kinases (RTKs) have revealed unexpected diversity in the mechanisms of their activation by growth factor ligands. Strategies for inducing dimerization by ligand binding are surprisingly diverse, as are mechanisms that couple this event to activation of the intracellular tyrosine kinase domains. As our understanding of these details becomes increasingly sophisticated, it provides an important context for therapeutically countering the effects of pathogenic RTK muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
3,618
4
25

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 4,831 publications
(3,793 citation statements)
references
References 144 publications
40
3,618
4
25
Order By: Relevance
“…Upon binding of its ligand (epidermal growth factor, EGF) the receptor undergoes a conformational change into an open conformation allowing association of two EGFR molecules into a dimer. Dimerization then leads to autophosphorylation of tyrosine residues in the intracellular domain (4)(5)(6). This model has been supported by crystal structures of the extracellular domain of EGFR (7,8) as well as by reports of EGFR dimerization after stimulation with EGF.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Upon binding of its ligand (epidermal growth factor, EGF) the receptor undergoes a conformational change into an open conformation allowing association of two EGFR molecules into a dimer. Dimerization then leads to autophosphorylation of tyrosine residues in the intracellular domain (4)(5)(6). This model has been supported by crystal structures of the extracellular domain of EGFR (7,8) as well as by reports of EGFR dimerization after stimulation with EGF.…”
Section: Introductionmentioning
confidence: 69%
“…The existence of preformed dimers, their relative amount in resting cells, and their role in EGFR signaling continue to present open questions and the findings of individual studies differ considerably (9,14). While some authors report negligible amounts of preformed dimers (15), others have found most EGFR molecules in dimeric form (6,9,16,17). Nagy et al (18) observed preformed dimers only at high expression levels of EGFR of ~600,000 receptors per cell.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that this gene plays a pivotal role in a variety of biology processes in both prokaryotes and eukaryotes, including cell signalling [35], cell division, protein export, membrane transport, DNA repair, and multidrug resistance in tumours [36,37]. The functional range of the nucleotide binding protein family is gradually expanding with the accession of some new members.…”
Section: Discussionmentioning
confidence: 99%
“…All RTKs possess a similar molecular architecture with three key features: an extracellular ligand binding domain, a transmembrane domain and a cytoplasmic kinase domain. In the human genome there are 58 known RTKs which are subdivided in 20 families according to structure of their extracellular domain (For review see [3]). RTKs function to transduce signals from extracellular stimuli by inducing changes in tyrosine phosphorylation that promote the formation of signaling complexes leading to changes in biological processes.…”
Section: Introductionmentioning
confidence: 99%